IT governance practices model in IT project approval and implementation in Malaysian public sector - Maidin, Siti Sarah; Arshad, Noor Habibah (2010)
In this global era, IT investment is rapidly increasing. IT governance practices must be emphasized in order to retrieve competitive advantage from IT investment. The aim of this research is to develop IT governance practices model for Malaysian public sector. Interview sessions with IT personnel at management level at Putrajaya were conducted. Based on the interviews, a theoretical model of IT governance which consists of senior management involvement in IT, corporate performance measurement systems, corporate communications systems, risk management, strategic alignment, value delivery, ethics/culture of compliance and resource management was constructed. Thus the structure, process and mechanism involved in each of the entities in the model could assist Malaysian public sector to inculcate IT governance practices in their operations in order to sustain competitive advantage.